UTILIZATION OF REMOTE SENSING TECHNOLOGY AND GEOGRAPHIC INFORMATION SYSTEMS FOR TOURISM DEVELOPMENT - Riki Ridwana; Shafira Himayah (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
The success of tourism in any country depends on the country's ability to develop, manage and market its tourism facilities and activities. Tourism development and management can be done in various ways. One of the most effective and efficient ways is to utilize remote sensing technology and geographic information systems (GIS). This article was created to archive and review some of the findings of the use of remote sensing technology and GIS for tourism management and development, using the literature review method. The use of remote sensing technology and GIS for tourism development and management has been widely used by various academics and researchers in various countries in the world including in Indonesia. This is acceptable because it is considered effective and efficient, the suitability of tourism development studies, for the study of tourism multimedia development, identification of the most desirable tourist areas, and for the evaluation of ecotourism areas.